PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DAN MOTIVASI BELAJAR DENGAN METODE PROBLEM SOLVING - Erna Sari Agusta (LPMP Provinsi DKI Jakarta, 2022)
As a subject that is considered difficult, it causes some students to be less motivated in learning mathematics. This is marked by a lack of enthusiasm and less active students to take PBM in class. In addition, the lack of problem solving skills makes students only able to solve problems based on the examples given. This is evidenced by the percentage of test scores of students who have not reached the KKM more than 75%. This study aims to determine the improvement of problem solving abilities and students' motivation to learn mathematics with the application of problem solving methods. This research uses Classroom Action Research (CAR) in two cycles consisting of design, activities and observations, reflection, and revision. The research subjects were students of class IX-1 MTsN 28 Jakarta. The data were obtained from the results of student motivation questionnaires, formative test results, and observation sheets for teaching and learning activities. The data were analyzed descriptively qualitatively by using an analytical technique framework consisting of data reduction, data presentation, and drawing conclusions. The results showed that the average value of students' mathematical problem solving abilities increased from the first cycle of 61.05 to 75.97 in the second cycle. The number of students whose scores are above the KKM also increased from 47.32% in the first cycle to 83.3% in the second cycle. Likewise, the number of motivated students increased for the medium, high, and very high categories from cycle I to cycle II. The conclusion of this study is that problem solving methods can improve motivation and mathematical problem solving abilities of students in class IX-1 MTsN 28 Jakarta.